Zhuangzi and collaboration in animals: a critical conceptual analysis of shared intentionality - Papadopoulos, Dennis (Frontiers in Psychology, 2023)
Shared intentionality is a specific form of shared agency where a group can be understood to have an intention. Michael Tomasello and colleagues (2005) conjectured that humans are better equipped for collaboration than other animals because humans but not other great apes share intentions. Exporting shared intentionality from a debate about the ontology of mental state attributions like intentions to groups may not seamlessly lend itself to evolutionary science. To explore and de-center the presuppositions of Western conceptions of cooperation, I look at Zhuangzi’s philosophy of action. Mercedes Valmisa (2021) explains the actions of individuals as always a form of co-action alongside other agencies to whom one must adapt. Thinking of cooperation as a product of co-action, not shared intention, sidesteps asking about the kinds of cooperation and directs attention to the know-how and behavioural flexibility needed to make our constant coordination adaptive.